Munc13-1 acts as a priming factor for large dense-core vesicles in bovine chromaffin cells - Ashery, Uri (Oxford University Press, 2000)
In chromaffin cells the number of large dense-core vesicles (LDCVs) which can be released by brief, intense stimuli represents only a small fraction of the ‘morphologically docked’ vesicles at the plasma membrane. Recently, it was shown that Munc13-1 is essential for a post-docking step of synaptic vesicle fusion. To investigate the role of Munc13-1 in LDCV exocytosis, we overexpressed Munc13-1 in chromaffin cells and stimulated secretion by flash photolysis of caged calcium. Both components of the exocytotic burst, which represent the fusion of release-competent vesicles, were increased by a factor of three. The sustained component, which represents vesicle maturation and subsequent fusion, was increased by the same factor. The response to a second flash, however, was greatly reduced, indicating a depletion of release-competent vesicles. Since there was no apparent change in the number of docked vesicles, we conclude that Munc13-1 acts as a priming factor by accelerating the rate constant of vesicle transfer from a pool of docked, but unprimed vesicles to a pool of release-competent, primed vesicles.